Corporate Criminal Liability In Tax Crimes From The Perspective of The Strict Liability Doctrine - Kyagus Ramadhani; Tunggul Anshari SN; Prija Djatmika (Faculty of Law, Merdeka University Surabaya, Indonesia, 2027)
Tax crimes are a form of economic crime that has the potential to cause significant losses to state revenues. The development of corporate activity as a major component of economic activity indicates that various tax crimes are no longer committed individually, but rather through policies and systems developed by corporations. However, Law Number 28 of 2007 concerning General Provisions and Procedures for Taxation and Law Number 7 of 2021 concerning the Harmonization of Tax Regulations do not explicitly regulate corporations as subjects of criminal law that can be held accountable. This situation creates a legal vacuum, legal uncertainty, and suboptimal protection of state finances. This study aims to analyze the urgency of regulating corporate criminal liability in tax crimes, examine the relevance of applying the strict liability doctrine as the basis for corporate criminal liability, and formulate an ideal legal regulation formulation for the future. This study uses a normative juridical method with a statutory, conceptual, and case-based approach. Legal materials were obtained through a literature review of laws and regulations, court decisions, legal literature, and scientific journals. The materials were analyzed using systematic and grammatical interpretation. The findings indicate that the lack of regulations regarding corporate criminal liability hampers the effectiveness of tax law enforcement and the recovery of state revenue losses. The strict liability doctrine is relevant for limited application to certain tax crimes while still adhering to the principle of due process of law. Legal reform through a revision of the KUP Law is needed to recognize corporations as subjects of criminal law and to comprehensively regulate accountability mechanisms, types of sanctions, and case resolution to ensure legal certainty, justice, and protection of state finances.